A cane improves postural recovery from an unpracticed slip during walking in people with Parkinson disease - Rumpa Boonsinsukh (2018)
Background. Little is known about the effects of use of a cane on balance during perturbed gait or whether people with Parkinson disease (PD) benefit from using a cane. Objectives. The purpose of this study was to evaluate the effects of cane use on postural recovery from a slip due to repeated surface perturbations in individuals with PD compared with age-and sex-matched individuals who were healthy. Design. This was a prospective study with 2 groups of participants. Methods. Fourteen individuals with PD (PD group) and 11 individuals without PD (control group) walked across a platform that translated 15 cm rightward at 30 cm/s during the single-limb support phase of the right foot. Data from 15 trials in 2 conditions (ie, with and without an instrumented cane in the right hand) were collected in random order. Outcome measures included lateral displacement of body center of mass (COM) due to the slip and compensatory step width and length after the perturbation. Results. Cane use improved postural recovery from the first untrained slip, characterized by smaller lateral COM displacement, in the PD group but not in the control group. The beneficial effect of cane use, however, occurred only during the first perturbation, and those individuals in the PD group who demonstrated the largest COM displacement without a cane benefited the most from use of a cane. Both PD and control groups gradually decreased lateral COM displacement across slip exposures, but a slower learning rate was evident in the PD group participants, who required 6, rather than 3, trials for adapting balance recovery. Limitations. Future studies are needed to examine the long-term effects of repeated slip training in people with PD. Conclusions. Use of a cane improved postural recovery from an unpracticed slip in individuals with PD. Balance in people with PD can be improved by training with repeated exposures to perturbations. © 2012 American Physical Therapy Association.